Author World's View in Sabariah Novel: Study of Lucien Goldmann's Genetic Structuralism - Syafri MaiBoy; Khairil Anwar; Ferdinal Ferdinal (Politeknik Negeri Padang, 2021)
This research discusses the worldview of the author in the novel Sabariah with the approach of Lucien Goldmann's genetic structuralism theory. Hamka's work was first published in 1928 with an Arabic-Minangkabau script. After being lost from circulation for decades in 2019, Gema Insani has republished the novel, still with the same time and atmosphere as 1928, but already in Indonesian. Researchers explore the genesis and world view of the author in the novel. The unique thing is that the Sabariah novel was previously published in kaba-style Arabic-Minangkabau script. Hamka's first novel is different from his later novels. They have followed the official spelling of the Dutch East Indies government. This research uses Lucien Goldmann's dialectical method that works reciprocally from part to whole. The novel Sabariah originates from the genesis of the bakaba tradition in Minangkabau which inspired the birth of the novel Sabariah, a phenomenon that often occurs at that time when many women fate are hanged without strings, which led to the birth of the fasakh of marriage which was initiated by Islamic reform scholars in Minangkabau. One of the characters is Haji Abdul Karim Amrullah, Buya Hamka 's father.The phenomenon of being hung without strings is also reflected in the novel Sabariah which is experienced by the character Sabariah himself, which causes polemics between characters. The worldview of the author in the novel Sabariah is the world view of humanism and religion.